(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Two-Photon Polymerization (2PP) is one of the most versatile techniques for additive microfabrication, allowing for the direct creation of true 3D meso- and microscale objects with sub-micrometer features, and either optically smooth or deliberately structured surfaces. After a short introduction of the technology, this presentation will show examples from the fields of cell scaffolds, tissue engineering, and organ-on-a-chip. In recent years, we have developed some significant advancements in 2PP, which I will review, including Aligned 2-Photon Lithography (A2PL) [1], Two-Photon Grayscale Lithography (2GL) [2], and 3D printing by 2GL [3]. With A2PL, one can 3D microprint components onto pre-structured surfaces, e.g., into microfluidic channels or chambers. The components are printed with sub-micron positioning accuracy. The rotation and tilt of the substrate are detected and corrected for as well. 2GL overcomes the fundamental trade-off of 3D printing, the trade-off between printing speed and surface quality, by dynamically modulating the laser power and thus the size of the exposed volume pixel or "voxel". First introduced for grayscale image (undercut-free) based printing in 2019, we recently launched the generalization of the 2GL technique to 3D printing, considerably improving printing speed and surface quality for complex 3D microstructures. To demonstrate the utility of 2GL for biological applications, I will show some results from a recent study of cell-material interaction with AI generated micro- and nano-surface topographies, inspired by Schamberger et al. (2022) [4], Unadkat et al. (2011) [5], and Callens et al. (2023) [6]. Author’s statement Conflict of interest: The author and coworkers are employed at Nanoscribe GmbH & Co. KG. References [1] M. Trappen et al. Aligned multiphoton lithography. Advanced Fabrication Technologies for Micro/Nano Optics and Photonics XV, vol. PC12012, p. PC120120N, Mar. 2022 [2] A. Bertoncini et al. Advancement in two-photon grayscale lithography. 3D Printed Optics and Additive Photonic Manufacturing III, vol. PC12135, p. PC1213501, May 2022 [3] M. Thiel et al. Advancement in two-photon grayscale lithography. Advanced Fabrication Technologies for Micro/Nano Optics and Photonics XVI, vol. PC12433, p. PC124330B, Mar. 2023 [4] B. Schamberger et al. Curvature in Biological Systems: Its Quantification, Emergence, and Implications across the Scales. Advanced Materials vol. 35, p. 2206110, 2023 [5] H. V. Unadkat et al. An algorithm-based topographical biomaterials library to instruct cell fate. Proceedings of the National Academy of Sciences vol. 108, pp. 16565–16570, Oct. 2011 [6] S. J. P. Callens et al. Emergent collective organization of bone cells in complex curvature fields. Nat Commun vol. 14, p. 855, Mar. 2023